KAJIAN YURIDIS TERHADAP PERATURAN KEPALA KEPOLISIAN REPUBLIK INDONESIA NOMOR 14 TAHUN 2012 TENTANG MANAJEMEN PENYIDIKAN TINDAK PIDANA TERKAIT PROSES PENYIDIKAN SUATU PERKARA TINDAK PIDANA - M.Hum, Dr. Drs. M.S Chandrajaya (Kerta Dyatmika, 2017)
The management of criminal investigation becomes very important because limited resources, such as personnel, time, materials, and funds must be mobilized in a planned, organized and controlled manner so that effective and efficient investigations are realized and ultimately realize the objectives of the Police forward, there will be standard operating procedures for each stage of the investigation to be applied throughout the Police. The formulation of the first problem How is the process of investigation of a criminal case based on the regulation of Chief Police Republic Indonesia Number 14 Year 2012 ?, the second What is the weakness of the investigation after the formation of the regulation of Chief Police Number 14 Year 2012 ?, legal research used is normative legal research, using the approach of legislation, Sources of legal materials used are; Source of primary, secondary, and tertiary law materials, techniques of collecting legal materials using literature study, to analyze the legal materials that have been collected then used several techniques of analysis that is description, interpretation, evaluation, and argumentation techniques.Based on the research can be drawn conclusion as follows; The process of investigation of criminal cases according to the Regulation of the Chief of Police Number 14 Year 2012 on Management of Criminal Investigation is divided into four sections: first planning, second organizing, third implementation consisting of Investigation, SPDP (Notice of Commencement of Investigation), Forced Effort, Completion of Case Files, Submission of Case Files, Submission of Suspects, Evidence,, Termination of Investigation and all four supervision and control. The weakness of the investigation after the enactment of Chief Police Republic Indonesia Regulation Number 14 Year 2012 on Criminal Investigation Management can be seen from external factors and internal factors.Â Keywords : Juridical Study The Regulation Of The Chief Police Republic Indonesia Number 14 Year 2012, Process of Investigation,